Seventh to eleventh century CE glass from Northern Italy: between continuity and innovation - Bertini, Camilla; Henderson, Julian; Chenery, Simon (Springer, 2020)
Previous analytical studies show that most of Northern Italian glass has been heavily recycled and that mixing of natron and plant ash glass was occurring (Verità and Toninato 1990; Verità et al. 2002; Uboldi and Verità 2003; Andreescu-Treadgold and Henderson 2006; Silvestri and Marcante 2011). The re-use of “old Roman glass” has been interpreted as stagnation in glass trade from the primary production areas. However, the reintroduction of plant ash glass on sites such as Torcello, Nogara, and in Lombardy at the same time as it was reintroduced in the Levant, strongly indicates long-distance contacts with the Levant at least from the eighth century CE. This paper addresses the key issue of recycling by focusing on the compositional nature of glass traded and reworked in Northern Italy after the seventh century CE set in a broad Mediterranean context by analysing major, minor, and trace elements in eighty-nine glass samples (seventh to the eleventh century AD) from the glass workshop of Piazza XX Settembre, Comacchio. Five major previously proposed compositional groups of glass have been identified from Comacchio (Levantine Apollonia and Jalame types, HIMT, Foy-2, and plant ash glass). The impact of recycling and mixing practices in Comacchio glass is also discussed with the help of known recycling markers and selected ratios (major and trace elements). The mixing between Levantine, HIMT, and plant ash glass is highlighted and end-members of potential natron to natron mixing compositional groups have been identified. The compositional nature of plant ash glass from Northern Italy is discussed in light of their trace element content and production areas.